(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
The article examines the importance of developing communicative competence in future engineers. It is emphasized that to create an effective training model, it is necessary to deeply analyze the communicative requirements of the modern engineering profession. The key components of an engineer’s communicative competence are described, including proficiency in technical language and discourse, interpersonal communication skills, professional writing literacy, the ability to make oral presentations, cultural competence, and ethical communication. A comprehensive approach is proposed for developing these multifaceted skills in engineering students for their successful professional activities.